Decrease in Global Offset Leads to Complaints of Worsening of Valgus Knee Deformity After Total Hip Arthroplasty in Patients With Crowe Type IV Developmental Dysplasia of the Hip - Minzhi Yang; Xiangpeng Kong; Ping Song; Zheng Cao; Wei Chai (Orthopaedic Surgery)
ABSTRACT Background Conflicting evidence exists regarding the impact of total hip arthroplasty (THA) on valgus knee deformities in patients with developmental dysplasia of the hip (DDH). The aim of this retrospective study was to identify the factors potentially contributing to the worsening of valgus knee deformities in DDH patients after THA. Methods This retrospective case–control study included 51 patients (69 hips) with Crowe type IV DDH who underwent primary THA between January 2018 and January 2020. The anatomic lateral distal femoral angle (aLDFA), mechanical lateral distal femoral angle (mLDFA), anatomic medial proximal tibial angle (MPTA), hip–knee–ankle (HKA) angle, anatomic tibiofemoral angle (TFA), joint line convergence angle (JLCA), tibial joint line angle (TJLA), femoral offset (FO), acetabular offset (AO), global offset (GO), and extent of leg lengthening were measured before and after THA. The case group comprised patients who complained that their valgus knee deformity worsened after THA, and the control group comprised those who did not. Hip‐level data were compared using generalized linear mixed effects models for proportions/rates and linear mixed models for means. Results The case group has 19 hips, and the control group has 50 hips. Both groups showed improvement in the HKA after THA (p < 0.05), but the case group presented with a smaller HKA (177.4 ± 2.4 vs. 175.2 ± 2.7, p < 0.001) and greater AO (5.8 ± 1.0 vs. 5.0 ± 1.0, p = 0.011) and GO (7.9 ± 0.7 vs. 7.0 ± 1.1, p = 0.003) values before THA. After THA, GO decreased in both groups, and the TJLA increased in the case group (0.6 ± 2.6 to 2.3 ± 3.5, p = 0.011). Conclusions THA improved the HKA in DDH patients. However, a decrease in GO could lead to an increase in the TJLA, suggesting pseudoprogression of the valgus knee deformity and therefore lead to complaints of worsening of valgus knee deformities. GO restoration during surgery may reduce the impact on the TJLA.